2016
DOI: 10.1016/j.otsr.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

A new procedure for fractures of the medial epicondyle in children: Mitek® bone suture anchor

Abstract: We present a new bone suture anchor technique for fractures of the medial epicondyle. The hypothesis was that the results would be similar to those with the divergent K-wire fixation. This retrospective study included 40 patients who presented with displaced fractures of the medial epicondyle: one group was treated with a Mitek(®) non-resorbable bone suture anchor (group A: n=21), the other by K-wire fixation (group B: n=19). A medial approach was taken with an anchor placed above the olecranon fossa. The epic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…As discussed in a previously published bone anchor suture repair technique 13 , the authors suggest that the use of the proposed suture bridge technique would not require subsequent hardware removal due to irritation, seen with k-wire or screw fixation 15 . PEEK anchors are a nonabsorbable, strong, and radiolucent anchor that retains strength during the critical phases of tissue healing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As discussed in a previously published bone anchor suture repair technique 13 , the authors suggest that the use of the proposed suture bridge technique would not require subsequent hardware removal due to irritation, seen with k-wire or screw fixation 15 . PEEK anchors are a nonabsorbable, strong, and radiolucent anchor that retains strength during the critical phases of tissue healing.…”
Section: Discussionmentioning
confidence: 98%
“…Medial epicondyle fractures constitute 11% to 20% of fractures around the elbow. Surgical options that have been described for fixation of medial epicondyle fractures include the use of sutures, K wires, cannulated screws with and without washer, suture anchor repair or excision of the fragments with advancement of medial soft tissues 6 , 11 , 13 . Hardware irritation is one of the disadvantages of wire or screw fixation that might need surgical removal.…”
mentioning
confidence: 99%
“…Thelen et al used bony anchor sutures for fixation, while Poircuitte [ 12 also employed PLGA pins for stable internal stabilization. [ 13 ] Su and Nan [ 14 ] reported that self-reinforced polylactide pins showed better short-term functional outcomes than K-wires.…”
Section: Discussionmentioning
confidence: 99%
“…Displaced medial epicondyle fractures can be treated with a variety of implants, such as different techniques of K-wires, screws, and tension band wires. [10][11][12][13][14] Excision of the fragment and soft tissue reattachment have poor outcomes. [11] Most surgeons prefer open reduction because the ulnar nerve is close to the fracture and closed techniques may cause iatrogenic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…A Bioglass coating improves the structural integrity of the composite by controlling the biodegradation rate and protecting it from some degradation. J.J [131] reported that a different silver doped bioactive glass powder was applied to resorbable and non-resorbable vicryl polymer sutures to improve its microbial activity, bioactivity, and bactericidal activities [132]. In this technique, silver bromide (AgBr) particles in deionized water were stirred continuously to prevent sedimentation.…”
Section: Common Biomaterials For Uhmwpe Graft Modificationmentioning
confidence: 99%